Pendidikan Agama Islam dalam Implementasi Kurikulum Merdeka di Sekolah dan Madrasah: Islamic Religious Education in the Implementation of Independent Curriculum at Schools and Madrasah - Lailatul Afiyah; Anfa Regita Ayu Pratiwi; Maulidatuzzahro’ (STAI Ma'had Aly Al-Hikam Malang, 2024)
The Minister of Education, Culture, Research and Technology (Mendikbudristek) addressed education problems in Indonesia by issuing the Independent Curriculum policy to replace the 2013 Curriculum. As a new policy, many academics and stakeholders do not fully understand the Independent Curriculum. This article was prepared based on a literature study, with a focus on studying Islamic Religious Education (PAI) in the Implementation of the Independent Curriculum in Schools/Madrasahs. There are four article findings. First, the Graduate Competency Standards (SKL) are divided into four levels: a) PAUD or RA; b) SD/MI; c) SMP/MTs; d) SMA/SMK/MA. Second, PAI Learning Outcomes (CP) must be used as a reference for preparing Learning Objectives (TP) and Learning Objective Flow (ATP) which include elements of the Al-Qur'an, Hadith, Aqidah, Akhlak, Fiqh and the History of Islamic Civilization (SPI). Third, The development of PAI Teaching Modules is structured based on components, principles and procedures that have been established by each educational institution. Permasalahan pendidikan di Indonesia disikapi Menteri Pendidikan, Kebudayaan, Riset, dan Teknologi (Mendikbudristek) dengan mengeluarkan kebijakan Kurikulum Merdeka sebagai ganti dari Kurikulum 2013. Sebagai kebijakan yang baru, maka banyak civitas akademika maupun stakeholders yang belum paham sepenuhnya mengenai Kurikulum Merdeka. Artikel ini disusun berdasarkan studi pustaka, dengan fokus kajian Pendidikan Agama Islam (PAI) dalam Implementasi Kurikulum Merdeka di Sekolah/Madrasah. Ada empat temuan artikel. Pertama, Standar Kompetensi Lulusan (SKL) terbagi menjadi empat jenjang: a) PAUD atau RA; b) SD/MI; c) SMP/MTs; d) SMA/SMK/MA. Kedua, Capaian Pembelajaran (CP) PAI harus dijadikan sebagai acuan untuk penyusunan Tujuan Pembelajaran (TP) dan Alur Tujuan Pembelajaran (ATP) yang meliputi elemen Al-Qur’an Hadis, Akidah, Akhlak, Fikih dan Sejarah Peradaban Islam. Ketiga, Pengembangan Modul Ajar PAI disusun berdasarkan komponen, prinsip dan prosedur yang sudah ditetapkan oleh masing-masing lembaga pendidikan. Kata Kunci: Kurikulum; Kebijakan PAI; Merdeka Belajar.